Atomistic-scale insights into the crosslinking of polyethylene induced by peroxides. (21st November 2019) - Akbarian, Dooman; Hamedi, Hossein; Damirchi, Behzad; Yilmaz, Dundar E.; Penrod, Katheryn; Woodward, W.H. Hunter; Moore, Jonathan; Lanagan, Michael T.; van Duin, Adri C.T.
Abstract: Dicumyl peroxide (DCP) is the most commonly used peroxide crosslinking agent for polyethylene (PE) in high voltage power cables. The DCP reactions in the PE matrix lead to the formation of a range of byproducts, some of which remain in the final crosslinked polyethylene (XLPE) product and may have adverse effects on the cable function and its long-term properties. In this study, we utilized ReaxFF based molecular dynamics (MD) simulations and experimental techniques including Fourier transform infrared (FTIR) mapping and wide-angle X-ray scattering (WAXS) to obtain detailed atomistic scale insight into peroxide-induced crosslinking of PE. Our results indicate that a moderate curing temperature rise to 500 K leads to an increased crosslinking extent, however, temperature rise above 500 K may have adverse effects on the PE crosslinking. Additionally, our results indicate that elevating the density improves the PE crosslinking. Our study showed that a high ratio of DCP to PE can increase the amount of generated byproducts but may not necessarily lead to an increased amount of XLPE. Our MD results also indicate that the presence of an external electric field had almost no effect on crosslinking and that di-(1-decyl-1-phenylundecyl) peroxide, may not be as efficient as DCP in XLPE production. These results indicate that ReaxFF based molecular dynamics, validated by experiments, is an efficient tool for analyzing – and improving – the conditions of polymerization chemistry. Graphical abstract: Image 10778 Highlights: ReaxFF based MD simulations, FTIR mapping and WAXS techniques were utilized to obtain insight into peroxide-induced crosslinking of PE. A moderate curing temperature leads to an increased crosslinking extent, however, temperature rise above 500 K may have adverse effects. A high ratio of DCP to PE can increase the amount of generated byproducts but may not lead to an increased amount of XLPE. DDPP, a functionalized version of DCP, may not be as efficient as DCP in XLPE production.